Age-related upregulation of p16 expression in mouse ovarian somatic cells correlated with reproductive function decline p16 expression and ovarian aging in mice - Yorino Sato; Yuta Kawagoe; Kazuhiro Kawamura (PLoS ONE, 2026)
Female reproductive aging is a major clinical challenge associated with declining fertility and increased pregnancy complications. The urgent clinical need for developing reliable biomarkers to evaluate ovarian aging has become increasingly evident. Cellular senescence, marked by p16, contributes to age-related tissue dysfunction. However, the relationship between p16 levels and ovarian aging remains poorly understood. Age-related changes in p16 levels across multiple tissues in ICR mice were examined in ICR mice at 4, 30, 45, and 60 weeks of age using qRT-PCR, ELISA, and immunohistochemistry. Cell-type specific p16 levels were analyzed in isolated ovarian cells. Reproductive function was assessed through superovulation, in vitro fertilization, and embryo transfer experiments. p16 mRNA levels increased progressively with age in ovarian tissue (6.8-fold increase at 60 weeks vs. 4 weeks, P < 0.05), with corresponding increases in p16 protein levels. Among tissues examined, ovaries, kidneys, liver, uterus, spleen, and pancreas showed significant age-related p16 upregulation, while brain, heart, and lung did not. Cell-type analysis revealed that somatic cells exhibited pronounced p16 upregulation with age (cumulus cells: 3.2-fold, granulosa cells: 4.6-fold, theca cells: 2.8-fold increase), whereas oocytes and blastocysts showed no significant changes. Ovulation numbers decreased significantly with age (42.3 ± 3.1 vs. 15.6 ± 1.9 oocytes in young vs. aging mice), but fertilization rates and early embryo development remained unaffected. However, post-implantation outcomes deteriorated substantially, with implantation rates declining from 78.4% to 38.1% and live birth rates from 82.3% to 43.2% in aging mice at 60 weeks of age. Age-related upregulation of p16 in ovarian somatic cells, but not in oocytes, correlated with declining reproductive function, particularly affecting post-implantation development. These findings suggest that somatic cell senescence may contribute to age-related declines in oocyte competence, leading to fertility decline with aging.